Parent-child attachment as a mediator and moderator of parent depressive symptoms and infant dysregulation - Cruz Castorena, Daniela, author; Rieker, Julie, advisor; Haddock, Shelley, committee member; Faw, Meara, committee member (Colorado State University. Libraries, 2024)
Maternal depression has been found to be a significant predictor of child developmental outcomes, often resulting in both internalizing and externalizing problematic behaviors (Cummings & Davies, 1994; Gelfand & Teti, 1990; Schiavo & Perosa, 2020). Although there are numerous studies observing the detrimental effects of mother depression on their children, less is known about the potential negative effects of father depression. Moreover, little is known about how fostering a secure attachment may act as a protective buffer (moderator) for children against these negative effects. The current study tested the extent to which parent-infant attachment influences the relationship between parental depression and infant dysregulation through moderating or mediating mechanisms. This longitudinal study involved following 300 mother-father-infant triads from 6 to 18 months of age. Parental depressive symptoms were measured using the General Depression subscale of the Inventory of Depression and Anxiety Symptoms (IDAS) at 6 months. Parent-infant attachment was coded based on observations from the Strange Situation at 16-months for fathers and at 18-months for mothers. The dysregulation subscale of the parent-reported Brief Infant-Toddler Social Emotional Assessment (BITSEA) was assessed at 16 and 18 months. Although a significant correlation was found showing that increased levels of mother depressive symptoms at 6 months was related to higher levels of mother-reported infant dysregulation, there were no significant results involving fathers, and no significant evidence of mediating or moderating influences of parent-infant attachment on the link between depressive symptoms and infant dysregulation.